2018
DOI: 10.3390/asi1030036
|View full text |Cite
|
Sign up to set email alerts
|

A TAM-Based Study of the Attitude towards Use Intention of Multimedia among School Teachers

Abstract: Multimedia teaching materials are widely applied in various disciplines. More resources are provided by authorities to encourage elementary school teachers to use them. The resources provide an opportunity for teachers to share teaching resources for students. In this study, the technology acceptance model (TAM) was used as the basic model to explore the effects of the information technology (IT) environment on the perceived usefulness, perceived ease of use, and attitude towards using multimedia, and the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
132
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(165 citation statements)
references
References 11 publications
25
132
2
6
Order By: Relevance
“…Based on the results of statistical tests conducted that perceived usefulness has a positive and significant effect on Mobile Payment. These results agree with the research conducted by (Kim, Mirusmonov, & Lee, 2010;Weng, Yang, Ho, & Su, 2018). The use of many DANA applications provides many benefits for users in conducting transactions.…”
Section: Perceived Usefulness On Mobile Paymentsupporting
confidence: 90%
“…Based on the results of statistical tests conducted that perceived usefulness has a positive and significant effect on Mobile Payment. These results agree with the research conducted by (Kim, Mirusmonov, & Lee, 2010;Weng, Yang, Ho, & Su, 2018). The use of many DANA applications provides many benefits for users in conducting transactions.…”
Section: Perceived Usefulness On Mobile Paymentsupporting
confidence: 90%
“…Sedangkan berdasarkan penelitian yang telah dilakukan oleh Santoso 2012 (Santoso, 2012) dan social influence (Taylor dan Todd,195). Attitude toward using berpengaruh langsung terhadap behavioral intention (Weng et al 2018). Hingga pada akhirnya behavioral intention berpengaruh terhadap Actual usage (Chau, 2010).…”
Section: Metode Penelitianunclassified
“…(terima H8). Hal tersebut sesuai dengan hasil penelitian yang dilakukan olehWeng et al (2018),Shabrina et al (2018) danSetiawati et al (2018), meskipun bertentangan dengan studiNugroho et al (2018).Perceived usefulness secara langsung berpengaruh signifikan terhadap behavioral intention. Semakin banyak manfaat yang didapat oleh nasabah dalam menggunakan internet banking maka akan memengaruhi minat pengguna untuk menggunakan kembali internet banking.…”
unclassified
“…Consistent with prior studies (Albirini 2006;Blau and Shamir-inbal 2017;Chang et al 2017;Hatlevik 2017), our study found that teachers who have more positive perspectives on current computer use in teaching and learning are likely to have positive perspectives on future smart learning as well. Therefore, it is necessary for teachers to have positive experiences with technology-based teaching and to learn even with a very simple tool based on the recent TAM model studies (Cheok and Wong 2015;Weng et al 2018). Developing and implementing new tools and materials in learning environments can be challenging for teachers.…”
Section: Discussionmentioning
confidence: 99%
“…They explained the general user's intention to accept technology with two determinants; perceived usefulness and perceived ease of use. Many recent technology user studies also develop the ideas from the TAM model (Cheok and Wong 2015;Teeroovengadum et al 2017;Weng et al 2018). In the same context, we assumed that when teachers have usefulness perspectives on the current computer-based teaching and learning or future smart learning, it would be positively related to their frequent ICT class adopting rate.…”
Section: Literature Reviewmentioning
confidence: 99%